THE FINANCIAL MECHANISM AS A FACTOR IN INCREASING THE EFFECTIVENESS OF SMALL BUSINESS (International journal of medical sciences, 2026)
The article examines pressing contemporary issues related to strengthening the impact of small business development on improving the financial efficiency of entrepreneurial activity. The main indicators of the level of entrepreneurship development are identified and analyzed. Based on practical materials, specific recommendations are provided for the formation of a civilized market environment and the achievement of optimal employment of the population.